GW24-e2389 Delivery of AAV9 cyclin-A2 via hyaluronic acid hydrogel induces cardiac regeneration as well as improves cardiac function in vivo post mycardial infarction. (1st October 2013) - Wen, Cao; Ma, Xiang; Zhao, Aichao; Yao, Yongzhao; Liu, Fen; Chen, Bangdang; Ma, Yitong
Abstract : Objectives: To assess the effects of exogenous AAV9 Cyclin-A2 with hyaluronic acid in vivo post MI. Methods: Forty-eight male Sprague Dawley rats were randomly divided into four groups: MI + PBS (n = 12); MI + AAV9 Cyclin-A2 (n = 12); MI + HA (n = 12); MI + HA + AAV-9 Cyclin-A2 (n = 12) . 2×10 12 genome copies in PBS or HA were injected into the infarcted myocardium at three different points around the infarcted regions. Echocardiography was performed to assess the left ventricular function. The hearts of each group were harvested four weeks post MI to assess gene expression, apoptosis, vascular density, infarct area, and cardiac function by Western Blot, immunohistochemistry, and Masson Triple Stain. Results: There was a significant statistical difference in expression of Cyclin-A2 and PCNA between HA + AAV9 Cyclin-A2 and two other control groups (MI + PBS and MI + HA) after four weeks. However, mitosis specific protein, H3P, had no statistical difference in expression among four groups (F = 7.6, p > 0.05). Strikingly, sequential delivery of AAV9 Cyclin-A2 increased EF compared with PBS alone (F = 15, p < 0.05) or HA blank (F = 33, p < 0.01), but no significant difference in the LVESD was observed between the groups. The values of LVEDD at four weeks were: PBS alone 1.16 ± 0.06; HA alone 1.13 ± 0.04; AAV9 Cyclin-A2 1.14 ± 0.05; and HA + AAV9 Cyclin-A2 1.29 ± 0.05 respectively. Meanwhile, the values of EF were: PBS alone 0.89 ± 0.03; HA blank 1.07 ± 0.12; AAV9 Cyclin-A2 0.98 ± 0.05, and HA + AAV9 Cyclin-A2 1.16 ± 0.06 respectively. Conclusions: HA can be used as a vehicle for gene delivery. AAV9 Cyclin-A2 with HA serve as a new approach in cardiac remodeling as well as promoting cardiomyocytes regeneration.